Country risk assessment methodologies: how risky are they? - Dans, Noemi (Papeles de Europa, 2014)
Unpredictable, subjective, elusive and difficult to lock in formal models are some adjectives that expert analysts have attributed the country risk. These traits are not surprising considering that behind the political risk is the complexity of the socio-political, economic and financial reality. Country risk in international trade affects solvency whereas in FDI is related to the losses caused by deprivation of property rights, cessation of activities or damage to assets. The country risk assessment is essential for multinational companies and for countries in the design of their development strategy. However, in view of its complexity, what is the most appropriate methodology for this kind of risk? Are econometric models appropriate? This article reviews and discusses various analysis methodologies and responds to these questions.
Keywords: Foreign direct investment; risk assessment; country risk